Ecotaurism through the Cultural Heritage of the Mekongga Kingdom in the Wundulako District - Koodoh, Erens E.; Laxmi, Laxmi; Hermina, Sitti; Rahman, Nurhidayah; Mansur, Runni Yanti (Postgraduate, University of Mataram, 2023)
The advent of globalization has resulted in changes in people's lifestyles that are more modern, resulting in people being more inclined to choose new cultures that are considered more practical than local cultures. One of the factors causing local culture to be forgotten nowadays is the lack of future generations who have an interest in learning and inheriting their culture. Therefore, the aim of writing this article is to explain the community's efforts to strengthen social status through the cultural heritage of the Mekongga kingdom. The data collection technique used in this research is Snowball Sampling through observation participation and in-depth interviews. This type of qualitative research uses ethnographic research methods. The results of this research show that the people in Wundulako District, known as the Mekongga people, strengthen their social status through the cultural heritage of the Mekongga Kingdom, namely by carrying out death ceremonies, Wonua mosehe cultural rituals, mesosambakai cultural rituals, mosehe cultural rituals within the royal family, and through Mekongga cultural games, namely Mepae-pae Festival with traditional game competitions such as Metinggo (engrang), Mehule (Gasing), Mebaguli (candlenut kernel marbles), and Mesuke (picking and hitting the stem).